Religious faith traditions tussle with rampant corruption toward sustainable development: Search for the missing links in light of ubuntu - E. Chinyena (Acta Theologica)
There is a raging debate in scholarly discourse on the role of religious faith traditions in influencing firm dispositions on various institutions and economic growth. Religious faith traditions are fighting rampant corruption that is drawing back socio-economic growth. The vice contradicts the religious faith principles of being virtuous. The church has a mandate to challenge and speak out against corruption. Corrupt tendencies permeate all institutions and cultures in the world, leading to general retrogression in sustainable development. This article aims to seek the missing links in empowering anticorruption officials in their stated targets. It investigates the achievements of the church in fighting all types and forms of corruption. The study adopts both quantitative and qualitative research methods. Interviews and questionnaires are the data-collection tools. A crosssectional survey study design was used to collect data from a stratified random sampling of 100 respondents by means of structured questionnaires in Harare, Zimbabwe. The church has a moral and social obligation to fulfil its prophetic mission of fighting corruption. This article analyses how the church can influence the state apparatus in the fight against corruption.